Odpowiedzi

2010-03-02T20:43:36+01:00
A) [(28 x 10 + 28 x 7)]- [(28 x 10 + 28 x 5)] = (280+196)- (280+ 140)= 476-420=56
b) [(134x100 + 134 x 30 + 134 x 5)] - [(133 x 100 + 133 x 50 + 133 x 5)]= (13400+ 4020+670)-(13300+6650+665)= 18090- 20615= (-2525) na minusie;P
c) [(31x10+ 31x5)] - [(62x5+ 62x2)]= (310+155) - (310+124)= 465- 434=31
d) [(12 x 10 + 12 x 3)] - [(6x20 + 6 x 6)]= (120+36)- (120+36)= 156-156=0
e) [(13 x 50 - 13 x 1)] - [(26 x 25 + 26 x 2)]= (650-13)-(650+52)= 637-702= (-65) na minusie;P
f) (52x52)- [(57x50 + 57 x 5)] = 2704- (2850+285)= 2704-3135= (-431) na minusie;P
Mam nadzieje że pomogłam
2010-03-02T20:44:30+01:00
A)28•17-28•15 = 28(17 - 15) = 28 * 2 = 56
b)123•135-133•135 = 135(123 - 133) = 135 * (-10) = -1350
c)31•15-62•7 = 31(15 - 2*7) = 31(15 - 14) = 31 * 1 = 31
d)12•13-6•26 = 13(12 - 6*2) = 13 * 0 = 0
e)13•49•27 = ?
f)57²-57•55 = 57(57 - 55) = 57 * 2 = 114
2010-03-02T20:45:50+01:00
A)28•17-28•15 = 28 (17-15) = 28 * 2 = 56
b)123•135-133•135 = 135 (123-133) = 135 * (-10) -1350
c)31•15-62•7 = 31 (15-3*7) = 31 (15-14) = 31 * 1 = 31
d)12•13-6•26 = 6(2*13 - 26) = 6* (26-26)= 6*0=0